Penggunaan Beberapa Isolat Khamir pada Fermentasi Biji Kakao - Susijahadi Susijahadi (agriTECH, 2000)
Effects of inoculation of eleven Yeast isolates, on the properties of cocoa beans during fermentations was studied. Inoculation of the eleven yeast isolates resulted different chemical properties of the bean comparing with the control. Isolates E, G, H, J, and K increased the temperature of the mass of the beans that of the control. Especially isolate H and I gave the optimal pH (5,26 and 5,25 respectively), resulting a high concentration of flavour precursors during fermentation. At the end of fermentation isolate H gave the highest concentration of total nitrogen (2,56%) and lipid (48,74%), whereas isolate I gave highest concentration of reduction sugar (2,71%) in cotyledon of the beans. Therefore inoculation of yeasts, especially isolate H and I, could improve the chemical properties of cocoa beans during fermentation.